Elevated anxiety and antidepressant-like responses in serotonin 5-HT(1A) receptor mutant mice - Heisler, Lora K. (The National Academy of Sciences, 1998)
The brain serotonin (5-hydroxytryptamine; 5-HT) system is a powerful modulator of emotional processes and a target of medications used in the treatment of psychiatric disorders. To evaluate the contribution of serotonin 5-HT(1A) receptors to the regulation of these processes, we have used gene-targeting technology to generate 5-HT(1A) receptor-mutant mice. These animals lack functional 5-HT(1A) receptors as indicated by receptor autoradiography and by resistance to the hypothermic effects of the 5-HT(1A) receptor agonist 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT). Homozygous mutants display a consistent pattern of responses indicative of elevated anxiety levels in open-field, elevated-zero maze, and novel-object assays. Moreover, they exhibit antidepressant-like responses in a tail-suspension assay. These results indicate that the targeted disruption of the 5-HT(1A) receptor gene leads to heritable perturbations in the serotonergic regulation of emotional state. 5-HT(1A) receptor-null mutant mice have potential as a model for investigating mechanisms through which serotonergic systems modulate affective state and mediate the actions of psychiatric drugs.